Analysis of Dynamic Change and Driving Factors of Ecological Footprint of Water Resources in Yunnan Province - ZHENG Tao; MI Zhijuan; XIE Yinchang (Renmin Zhujiang)
In order to ensure the coordination of water resources utilization and economic development in Yunnan Province,the sustainable planning and management of water resources in Yunnan Province should be strengthened.This paper analyzes the dynamic changes of water-resources ecological footprint in Yunnan Province from 2006 to 2018 through the ecological footprint model of water resources,and its driving factors by combining the LMDI decomposition method.The results show that:The total ecological footprint of water resources in Yunnan Province increased steadily and slowly as a whole.In the water utilization structure,the production water accounts for the largest proportion,with the highest ecological footprint,and followed by the domestic water,and the ecological water.From 2006 to 2018,the ecological carrying capacity of water resources in Yunnan Province showed a fluctuating trend,which increased overall after 2011.The water resources in Yunnan Province were in a state of ecological surplus,the same as that in all prefectures and cities.Among them,Kunming,Yuxi,and Chuxiong are on the verge of an ecological deficit,and the ecological footprint of water resources per 10 000 yuan of GDP is on the decline.Economic and technological factors play a leading role in the change of water-resources ecological footprint in Yunnan Province,among which economic factors play a positive role in driving the growth of water-resources ecological footprint.Therefore,it can be concluded that the water resources in Yunnan provinces is under a safe development and utilization state,with a great development potentiality.However,the distribution of water resources in different prefectures and cities is unbalanced,so it needs to be reasonably allocated.